A naturally occurring SNP modulates thermotolerance divergence among grapevines - Haiyang Chen; Haibo Yu; Ling Yuan; Lingchao Kong; Shenchang Li; Xiongjun Cao; Yang Li; Yi Wang; Ling Lin; Rongrong Guo; Taili Xie; Wei Duan; et al. (Nature Communications)
Abstract With the increasing challenges posed by global warming and climate change, heat stress has become a significant threat to the sustainable production of grapevines. However, the genetic basis of grapevine thermotolerance remains poorly understood. Here, we combine genome-wide association study with transcriptomic profiling to identify TTC4 (thermotolerance on chromosome 4), a gene encoding a WRKY transcription factor, as a key determinant of thermotolerance in grapevine. TTC4 directly activates two thermotolerance-related genes, HSP18.1 and APX3. We also identify a heat-suppressed repressor SPL13 (SQUAMOSA-promoter binding protein-like 13) that cannot bind to the GTAT element (TTC4 T(7631)) in intron 2 of TTC4, but can bind to the natural variant, GTAC (TTC4 C(7631)). Grapevine accessions with TTC4 C/C(7631) genotype exhibit significantly lower thermotolerance compared to those with the TTC4 T/T(7631) and TTC4 C/T(7631) genotypes. This fine-tuned regulation contributes to thermotolerance divergence among grapevine populations. The TTC4 T(7631) haplotype holds significant potential as a genetic resource for breeding thermotolerant grapevine varieties.